THE EFFECT OF COMBINATION OODEVWITHHCG ON OVULATION AND HATCHING OF FISH EGGOF AFRICAN CATFISH(Clarias gariepinusBurchell, 1822) - Damanik, Joyo Septian Jhonatan; Aryani, Netti; Alawi, Hamdan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of this research was to determine the effect of Oodev and HCG combination on ovulation and hatching of egg of Asian Catfish (Clarias gariepinus Burchel, 1822), Mutiara strain. This research was conducted from October-December 2018 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Faculty Riau University. An experimental design used in this experiment was Completely RandomizedDesign (CRD)with five treatments and three replications.The treatmentswere P1 (Oodev 0,5 ml/kg + 1000 IU/kg HCG), P2 (Oodev 0,5 ml/kg + 1500 IU/kg HCG), P3 (Oodev 0,5 ml/kg + 2000 IU/kg HCG), P4 (Oodev 0,5 ml/kg + 2500 IU/kg HCG), P5 (Oodev 0,5 ml/kg + 3000 IU/kg HCG). The result showed thatthe gave the shortest combinationOodev 0,5 ml/kg and3000 IU/kg HCG,latency period (6,27 hours), the highest of number of egg stripped(133 egg/g broodstock), ovisomatic index (17,45%), increased ofegg diameter (0,090 mm), increased egg maturation (14,44%), fertilization rate (87,35%), hatching rate (91,87%), and survival rate (90,67%). The water quality parameters during research was in optimal range temperature 22-30°C, pH 5-7and dissolved oxygen 3,23-5,20 mg/l. Keywords :Clarias gariepinus Burchell, 1822, Oodev, HCG, Ovulation, and Hatching rate